SmilieFace: Evolving Interface Design - Hengky; Marriott, Andrew; McMeekin, David (The Institute of Electrical and Electronics Engineers, Inc., 2012)
Smiliemail is an existing web-based application that enhances online communication by enabling users to create and send affective, engaging messages. It uses a computer generated video avatar, which articulates a sender's message that has been tagged using an XML markup language. With the advent of smart phones, a new less complex screen by screen interface was required due to their reduced screen size and power. A new Smiliemail client could also cater for the mobile paradigm of "media-rich communication everywhere".Interaction between users on Social Network Sites (SNS), such as Facebook often use emotional or affective communication. However, plain text messages, even if tempered with appropriate smilie icons, often cause misunderstanding, leading to flame wars or similar. Hence the Smiliemail affective avatars may provide an effective inter-user communication on SNSs. This case-study discusses the user interface evolution from the existing web-based Smiliemail interface, through to a smart phone interface, and finally to the SmilieFace Facebook application "canvas" interface. This study also details some Facebook application user interface and implementation issues.